Two dopamine D2-like receptor genes from the silkworm (Bombyx mori) and their evolutionary history in metazoan - Ping Chen (Nature Portfolio, 2017)
Abstract Dopamine is widely distributed in metazoans and is implicated in many physiological functions. Dopaminergic signaling is mediated through two classes of dopamine receptors, D1-like and D2-like. Phylogeny analysis reveals that, the dopamine receptors probably appeared ahead of the cnidarian divergence, two distinct classes of dopamine receptors likely formed prior to the separation of deuterostomes and protostomes, and INDRs probably split from its ancestor before the emergence of nematodes. Two D2-like genes are closely linked on the same scaffold, and the chromosome region around D2-like gene loci show colinearity among different species within Lepidoptera. These indicate two D2-like and their adjunction genes are likely Lepidoptera-specific orthologs, and occur by gene duplication event taken place after Lepidoptera ancestor split from the common ancestor of Lepidoptera and Diptera. In silkworm, two D2-like genes were expressed in examined tissues, and encoded BmDop2R2 having all the features of D2-like receptors and BmDop2R1 being a truncated variant without the region of N-terminal to TM II. Only dopamine distinctly lowered cAMP levels in BmDop2R2-expressing cells, whereas all tested amines for BmDop2R1 had not markedly effect in pharmacological test. These suggest there is functional difference between the two genes, which are likely resulted from subfunctionalization of gene duplication.